School zone: a problem analysis of student offending and victimization - Wilcox, Pamela (Temple University Press, 2022)
"This book combines offender, victim, and environmental perspectives to show how leading theories of crime are correctly and incorrectly applied to the school environment. It also evaluates data on a range of crimes at school ranging from theft to violence to verbal and physical assault and evaluates prevention strategies"--